ANALYSIS OF LIBRARIANS INTERPERSONAL COMMUNICATION AT PERPUSTAKAAN B. J. HABIBIE (International Conference on Social and Islamic Studies, 2021)
This research was conducted at the B.J Habibie Library of Politeknik Negeri Ujung Pandang. The problem that occurs in this research are the library staff (librarian) has been seen implementing unsuitable interpersonal communication such as not applying nonverbal communication i.e., expressions and eye contact to students (the librarians) and not trying to build communication with students. This study aims to determine how the interpersonal communication of staff (librarian) at the B.J Habibie Library. This type of research is descriptive with a population of 6,635 and the sample is drawn using the slovin method of 99 respondents. Then the data was collected through a questionnaire with a simple random sampling technique. From the results of the validity test of this study, it shows that there are 2 invalid indicators, namely the indicator of accepting input and appreciating, while the reliability test is 0.862. The results of the research that have been carried out show that during this pandemic the frequency of student visits to the library is 1-3 times a month and is dominated by grade 3 who come from the D3 Programme at Politeknik Negeri Ujung Pandang. Then the results of data analysis using quantitative analysis show that almost the indicators are in the good category, there is 1 very good indicator, namely equality. However, there are also indicators that have quite a lot of respondents answer neither agree nor disagree i.e., familiarity, willingness to cooperate and eye contact. But, overall, still in good category.